The Influence of Work Motivation and Discipline on Employee Performance: The Case of Central Statistics Agency of Karawang Regency - Muhammad Arif Fahrudin,; Asep Jamaludin,; Nandang,; Uus Mohammad Darul Fadli,; Shafie Mohamed Zabri, (Research in Management of Technology and Business, 2024)
The purpose of this study was to investigate the influence of work motivation and discipline on the performance of employees at the Central Statistics Agency of Karawang Regency. This study is quantitative and uses a causality method by conducting a survey among all 36 employees of the Central Statistics Agency of Karawang Regency indicating a non- probability sampling technique. Primary data obtained through the distribution of questionnaires were then analyzed using multiple regression, correlation, coefficient of determination, and hypothesis testing. Both work motivation and discipline were found to have a significant influence on employees’ performance. In other words, the higher the level of motivation and discipline of employees, the better their performance. The employees involved in the study were limited, so the results may not be generalizable to the entire population. The focus on work motivation and discipline may ignore other variables that are also significant in influencing employees’ performance, such as the work environment, leadership, or employee’s welfare. It is proposed to develop continuously performance appraisal system to monitor and measure the impact of motivation and work discipline policies and programs, and for the similar study to be conducted in other government agencies to compare the results to understand the differences and similarities in the effects of motivation   and discipline on employee performance This study can provide guidance to BPS management on how internal policies can be modified to improve work motivation and discipline , which in turn improves performance.